Coastal Water Quality in an Atlantic Sea Bass Farm Site (Sines, Portugal): A First Assessment - Gomes, Mara; Correia, Alexandre; Pinto, Lígia; Sá, Carolina; Brotas, Vanda; Mateus, Marcos (Frontiers in Marine Science, 2020)
Aquaculture has become the fastest-growing sector of the food industry worldwide. The increase of intensive aquaculture practices, however, has been raising global concern about economic and social impacts, but mostly due to the associated potential environmental impacts. The aim of this report is to make a preliminary assessment of the impact of an intensive sea bass aquaculture (Dicentrarchus labrax, L. 1758) on surrounding coastal waters. The aquaculture site is located at the SW Iberian coast (Sines, Portugal), having 16 cages, each holding approximately 150,000 specimens at different stages of growth. We present a spatial and temporal description of environmental physical, chemical, and biological parameters taken in the course of four monitoring campaigns conducted between June 2018 and April 2019. All monitored parameters, except phosphate concentration in October only at one sampling station, showed values within the desirable ranges for marine finfish production and the natural range of Portuguese coastal waters. So far, results do not reveal any detrimental impact of the production units on local water quality, although more research is needed. The preliminary findings suggest that the lack of stress on the receiving waters may be attributed to the hydrodynamic regime in the production area, the feeding strategy, and the dimension of the production.